Experimental investigation and field pilot testing of air assisted cyclic steam stimulation technique for enhanced heavy oil recovery. (1st August 2019) - Wang, Yanyong; Ren, Shaoran; Zhang, Liang; Deng, Junyu; Gong, Zhiwu; Hu, Changhao
Air assisted cyclic steam stimulation (AACSS) process is a novel technique for enhanced heavy oil recovery, which is efficient and economically attractive compared with other non-condensable gases and solvents injection-based techniques. In this study, the performance of AACSS process for an ultra heavy oil reservoir was investigated via laboratory experiments and field data analysis. The results indicate that air injection based on steam stimulation can effectively increase oil recovery in comparison with the conventional cyclic steam stimulation (CSS) process. The injected air can significantly increase and maintain the reservoir pressure, and reduce oil viscosity via flue gas dissolution and the thermal effect of low temperature oxidation (LTO) of the crude oil. The field pilot testing results of the AACSS technique in Liaohe Oilfield (Northeast China) demonstrate that AACSS can significantly increase oil production, prolong the effective production period of time, reduce water cut and the steam to oil ratio. A scoping economic study shows that the AACSS process can be more economically attractive than CSS process in terms of net present value. The AACSS technique has been effectively applied in mature heavy oil reservoirs developed by the conventional CSS, and it is also a feasible option to deep and offshore heavy oil reservoirs. [Received: January 6, 2017; Accepted: August 10, 2017]